A Case Report of Harlequin Ichtyosis - Shahrbanoo Salehin; Ahmad Azizimoghadam; Mohamad Babaeipour Divshali (Tehran University of Medical Sciences, 2012)
The harlequin fetus is the most severe type of congenital ichtyosis in which fetus suffers from chapped thick skin, abnormal face appearance, increased or decreased body temperature, respiratory distress, malnutrition, decreased sodium level, convulsion and infection. It happens once every 300 000 births in both genders. Premature birth and death are among consequences of this disorder. The woman was 31 years old. No abnormalities were reported in sonography. The fetus was delivered via normal vaginal delivery. The infant had a harlequin face appearance. The infant was discharged with consent of the parents after two days and passed away 24 hours after discharge.